The Effect of Artesunate and Brotowali (Tinospora Crispa) Combination on Histopathological, and Expression of Nuclear Factor Kappa B (NF-kÎ²) in Renal Tubules of Mice Infected With Plasmodium Berghei - Merici, Angela; Fitri, Loeki Enggar; Budiarti, Niniek (Universitas Brawijaya, 2020)
Brotowali (BR) extract (Tinospora crispa) can be used as an antimalarial. Aim: to determine the effect of BR extract in histopathological and expression of NFÎºB in mice tubules infected by Plasmodium berghei treated by artesunate (AR). Method: we used 42 C57BL / 6J strain mice as experimental animals, which were randomly divided into 7 groups : negative control (NC), positive control (PC), treatment group consist of AR 32 mg/kb (group 1); BR 70 mg/kg (group 2), combination of AR+BR 50 mg/kg (group 3), AR+BR 60 mg/kg (group 4), and AR+BR 70 mg/kg (group 5). Â Histological examination (hematoxylin-eosin (HE) staining) and expression of NFKB (immunohistochemical staining) in the kidneys were performed on 7th and 14th. Result: compared to PC group, BR with doses of 70 mg until 14th day, improved the degree of tubular necrosis, interstitial fibrosis, tubular degeneration, and inflammatory cell infiltration (p <0.001) but did not reach NC group (p <0.05). The combination of AR+BR until the 14thÂ day with dose of 50, 60, 70 mg all of dose improves significantly in-term of degree of tubular cell necrosis and inflammatory cell infiltration. The degree of interstitial fibrosis on 14th day only improved in group 4 and 5 (p<0.001 and p=0.003). The level of NF-kB expression on day 7 and day 14 was reduced in group 2, group 4, and group 5 compared to PC group. There was positive correlation on 7th and 14th between NF-kÎ² expression and tubular degeneration, tubular cell necrosis, inflammatory cell infiltration, and interstitial fibrosis. Conclusion: the combination of AR+BR extract can improve histopathological features and reduce NF-kÎ² expression in mice tubules infected by Plasmodium berghei with an optimal dose was 60 mg/day for 7-14 days or 70 mg for 7 days.